Non‐invasive Brain Stimulation Can Reduce Unilateral Spatial Neglect after Stroke: ELETRON Trial. Issue 3 (28th June 2022) - da Silva, Taís Regina; de Carvalho Nunes, Hélio Rubens; Martins, Laís Geronutti; da Costa, Rafael Dalle Molle; de Souza, Juli Thomaz; Winckler, Fernanda Cristina; Sartor, Lorena Cristina Alvarez; Modolo, Gabriel Pinheiro; Ferreira, Natalia Cristina; da Silva Rodrigues, Josiela Cristina; Kanda, Rafael; Fogarolli, Marcelo Ortolani; et al.
Abstract : Objective: Rehabilitation top‐down techniques based on brain stimulation present variable outcomes in unilateral spatial neglect (USN) after stroke. This study aimed to examine the effects of physical therapy after anodal and cathodal transcranial direct current stimulation (A‐tDCS and C‐tDCS, respectively) to improve visuospatial and functional impairments in individuals with USN after stroke. Methods: This double‐blinded, pilot randomized clinical trial enrolled patients with USN after ischemic stroke. Randomization was stratified according to the Behavior Inattention Test–Conventional (BIT‐C) and Catherine Bergego Scale (CBS). Outpatient physical therapy was conducted for 7.5 weeks after 20 minutes of tDCS. The primary outcome was the USN degree evaluated by the BIT‐C. Secondary outcomes were the difference in CBS score, stroke severity (National Institutes of Health Stroke Scale [NIHSS]), disability (modified Rankin Scale), autonomy (Barthel Index, Functional Independence Measure), and quality of life (EuroQol Group 5‐Dimension Self‐Report Questionnaire). Outcomes were analyzed using an analysis of covariance model corrected by age, baseline NIHSS, and baseline BIT‐C. Pairwise post hoc comparisons were performed using Bonferroni correction. Results: In the primary outcomes, A‐tDCS led to greater improvement in BIT‐C after intervention (mean difference [MD] = 18.4, 95% confidence interval [CI] = 3.9–32.8, p  = 0.008) compared to sham. However, no significant differences were observed between A‐tDCS and C‐tDCS (MD = 13.9, 95% CI = −0.3 to 28.1, p  = 0.057), or C‐tDCS and sham (MD = 4.5, 95% CI = −9.7 to 18.8, p  = 0.99). There were no significant differences between groups in terms of secondary outcomes. Interpretation: A‐tDCS associated with physical therapy can decrease the severity of USN after stroke. However, these preliminary findings must be confirmed by collecting additional evidence in a larger phase 3 trial. ANN NEUROL 2022;92:400–410